(untitled) - Ngumy, James G. (Sweden, 1992)
The book 'Agroforestry in Dryland Africa' (recorded here as COF/8/AFR/02) was published in 1988 and is wellknown as a useful and interesting among soil conservationists in Africa
Keywords: Agroforestry; Africa